1997
DOI: 10.1046/j.1365-2168.1997.02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition is superior to parenteral nutrition in severe acute pancreatitis: Results of a randomized prospective trial

Abstract: This study suggests that early enteral nutrition should be used preferentially in patients with severe acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
1
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(189 citation statements)
references
References 26 publications
3
176
1
9
Order By: Relevance
“…Furthermore, the concurrent administration of antibiotics might have a confounding effect, with almost all patients in our systematic review receiving antibiotics, which are known to increase the risk of diarrhoea during EN (36,37) . In addition, a number of RCT have demonstrated that EN in predicted severe acute pancreatitis is associated with the reduced blood glucose concentrations (25,26) , which in themselves may accelerate intestinal motility (41,42) and thus exacerbate diarrhoea in those receiving EN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the concurrent administration of antibiotics might have a confounding effect, with almost all patients in our systematic review receiving antibiotics, which are known to increase the risk of diarrhoea during EN (36,37) . In addition, a number of RCT have demonstrated that EN in predicted severe acute pancreatitis is associated with the reduced blood glucose concentrations (25,26) , which in themselves may accelerate intestinal motility (41,42) and thus exacerbate diarrhoea in those receiving EN.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three articles (21 articles containing patients suffering from SAP as well as 12 articles with MAP patients) were selected. They contained two nonrandomized and 31 randomized controlled clinical trials (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27]29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Finally, statistical analyses were performed on data from articles where both EN and NPO groups were presented, the trial was randomized, and the relevant data were available.…”
Section: Inclusions and Exclusionsmentioning
confidence: 99%
“…Seven out of seven articles contained analyzable data on mortal [16][17][18][19][20][21][22] Risk differences and CI were calculated in each article to analyze the effects of EN compared to the NPO nutrition. The calculated average risk difference (RD) was −0.050 (lower limit (LI): −0.134; upper limit (UI): 0.035; p-value: 0.249) (Figure 1).…”
Section: Severe Acute Pancreatitis (Sap) Groupmentioning
confidence: 99%
“…Windsor et al (1998) randomized thirty-four patients with acute pancreatitis to either TPN or EN and did not observe any difference in incidence of sepsis, length of hospital stay, computed tomography score or organ failure. Kalfarentzos et al (1997) randomized thirty-eight patients to either EN or TPN and showed that patients receiving TPN had a higher incidence of sepsis but did not increase the stay in the intensive care unit or the hospital. In this study, also, TPN did not increase the need for antibiotics or ventilator support.…”
Section: Pancreatitismentioning
confidence: 99%